Pemanfaatan Microsoft Office 2007 Dalam Apalikasi Perkantoran - Urfa, Mursalati; Nurbaiti, Nurbaiti (Universitas Labuhanbatu, 2023)
The rapid development of IT technology can help humans in completing human work ina ll fields. For example, in the field of education there is the use of microsoft offfice 2007 application in making tasks in the lecture process. Microsoft office is a part of Microsoft Office that is often used to handle Office applications. Maximum utilization of features can help facilitate and accelerate in handling the management of student tasks. Utilization of Microsoft 2007 on students in the use of making tasks, papers in maximizing the existing features in the application .Â applying Microsoft word to complete tasks given by lecturers at the state Islamic University of North Sumatra Medan.